Acculturation Strategy and its Influence on the use of Rhoticity by Polish Adult Immigrants to Wales - Matysiak, Aleksandra (Research in Language, 2022)
Migration to a foreign country can be a complex process involving the adjustment to a new culture and the acquisition of a second language (L2). Acculturation, the process by which an individual integrates their native values and behaviours with those of the host culture, is an integral part of this process. It has been suggested that the choice of acculturation strategy can either facilitate or hinder L2 acquisition (Schumann, 1986; Berry, 1997). Pronunciation is a vital aspect of L2 proficiency and is often seen as mediating an individual's identity in the host culture (Piske et al., 2001). This study focuses on the pronunciation patterns of ten adult Polish immigrants living in Welshpool, Wales, and attempts to examine the potential relationship between a chosen acculturation strategy (adaptation or preservation) and the use of rhoticity in English. Rhoticity, a salient feature of British English pronunciation that varies in use and quality depending on the region (Wells, 1982), has been previously studied in relation to the use of rhoticity by Polish speakers (Jaworski, 2010; Jaworski & Gillian, 2011; Stolarski, 2013, 2015; Zając, 2016; Rojczyk & Zając, 2017; Matysiak, 2020), with a notable emphasis on the use of taps in intervocalic and post-vocalic positions. The present study found some inconsistencies in the use of rhoticity in English.